2011
DOI: 10.1111/j.1439-0531.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Between the Porcine Morula and Blastocyst

Abstract: The survival and development of pre-implantation embryos are determinant factors affecting the outcome of animal reproduction. It is essential to transfer the expression of the genetic material from maternal sources, that is the ovum to the zygote before implantation to ensure successful development. Differentiation and transformation of blastomeres initiated during the morula and blastocyst stages is an important step of the embryonic development prior to implantation. We collected morula and early blastocyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Interestingly, when we examined enriched pathways for upregulated genes in vitri ed blastocysts, we observed important biological processes (cellular senescence and cell cycle) and signaling pathways (TGFβ, p53 and FoxO) that regulate the pluripotency of stem cells involved in embryo development and pregnancy. The enrichment of the TGFβ signaling pathway has also been reported in vitri ed porcine COCs [44,45], and upregulation of miRNAs related to this pathway was observed in vitri ed mouse blastocysts [61]. The upregulated genes in the TGFβ signaling pathway were BMPR1B, ID4, SMAD3 and TGFβ1, and there were also DEGs involved in the cell cycle pathway (CDKN1A) and signaling pathways regulating the pluripotency of stem cells (BMPR1B, ID4 and SMAD3).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, when we examined enriched pathways for upregulated genes in vitri ed blastocysts, we observed important biological processes (cellular senescence and cell cycle) and signaling pathways (TGFβ, p53 and FoxO) that regulate the pluripotency of stem cells involved in embryo development and pregnancy. The enrichment of the TGFβ signaling pathway has also been reported in vitri ed porcine COCs [44,45], and upregulation of miRNAs related to this pathway was observed in vitri ed mouse blastocysts [61]. The upregulated genes in the TGFβ signaling pathway were BMPR1B, ID4, SMAD3 and TGFβ1, and there were also DEGs involved in the cell cycle pathway (CDKN1A) and signaling pathways regulating the pluripotency of stem cells (BMPR1B, ID4 and SMAD3).…”
Section: Discussionmentioning
confidence: 61%
“…The most enriched GO terms in morulae were related to fatty acid and acyl-CoA metabolism. It is known that both fatty acids and acyl-CoA are metabolic switches linked to pluripotency that play an essential role in embryo development [44,45]. In addition, acyl-CoA controls crucial cellular processes such as mitosis, autophagy and energy metabolism, and this control is either direct or is mediated by epigenetic regulation of gene expression [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MLF1 may be a potential regulator of increased cellular apoptosis in DDB1-deficient porcine embryos, however further work is required. The morula is a pivotal period for blastocyst formation, controlled by a significant amount of differentially expressed genes between the morula and blastocyst stage (Hsu et al 2012). In this study, the most changed genes in the DDB1deficient morula were found to be associated with signal transduction, cell adhesion, and stem cell differentiation including YAP1 (also known as YAP).…”
Section: Discussionmentioning
confidence: 68%
“…These pathways regulate the pluripotency and pregnancy of stem cells involved in embryonic development. Enrichment of the signaling pathway has also been reported in vitrified porcine COCs ( 45 , 46 ), as well as in vitrified mouse blastocysts, indicated by increased level of miRNA that was associated with TGFβ upregulation ( 47 ). The FoxO pathway is also activated under stress conditions ( 48 ); FoxO molecules have been found in the inner cell mass of mouse blastocysts ( 49 ) to upregulate target genes, thereby promoting cell cycle stalled genes and increasing resistance to stress.…”
Section: Discussionmentioning
confidence: 87%